1984
DOI: 10.1210/endo-114-5-1617
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin-Stimulated Myosin Phosphorylation in Mammary Myoepithelial Cells: Roles of Calcium Ions and Cyclic Nucleotides*

Abstract: Oxytocin (10 nM) stimulated the phosphorylation of the 20,000 mol wt myosin light chain in rat mammary myoepithelial cells from a basal level of 0.17 to 0.85 mol phosphate/mol light chain within 30 sec. Of the smooth muscle stimulants tested, oxytocin appears to be the only normal physiological stimulus for myosin phosphorylation in these cells. The roles of cAMP, cGMP, and calcium ions were investigated in the mode of action of oxytocin and the regulation of myosin phosphorylation. Although oxytocin had no ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Olins and Bremel [11] have shown that OT exerts a double action on target cells: it activates contraction through myosin phosphorylation, and causes an increase in cytoplasmic cAMP [11]. However, while cell contraction is stimulated by OT concentrations in the range of 10 -9 M, the level of intracytoplasmic cAMP is only affected by OT concentrations in the range of 10 -8 or 10 -7 M or higher [20].…”
Section: Discussionmentioning
confidence: 99%
“…Olins and Bremel [11] have shown that OT exerts a double action on target cells: it activates contraction through myosin phosphorylation, and causes an increase in cytoplasmic cAMP [11]. However, while cell contraction is stimulated by OT concentrations in the range of 10 -9 M, the level of intracytoplasmic cAMP is only affected by OT concentrations in the range of 10 -8 or 10 -7 M or higher [20].…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy could be due to a variety of technical considerations (Arturi et al 2005). The oxytocin receptor is present in 50-90% of breast cancers (Bussolati et al 1996, Ito et al 1996, Sapino et al 1998 and is a G protein-coupled receptor capable of activating the G s -cAMP-protein kinase A (PKA) pathway (Olins & Bremel 1984) (Fig. 2).…”
Section: Nis Regulation In Breast Cancermentioning
confidence: 99%
“…The mode of contraction in myoepithelial cells involves an increase in [Ca 2+ ] i , and the subsequent activation of Ca 2+ -calmodulin-regulated myosin light chain kinase [32,33]. We previously demonstrated that oxytocin and ATP increase [Ca 2+ ] i and stimulate contraction in cultured mouse mammary myoepithelial cells [30].…”
Section: Introductionmentioning
confidence: 99%